Identifikasi Jenis Kupu-kupu (Lepidoptera) di Taman Wisata Alam Baning Kabupaten Sintang - Kurniawan, Azhar Armia; Samani, Kurnia Abdullah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Baning Nature Park is located on the Ana River, Sintang District, Sintang District, West Kalimantan Province, is an ex-situ conservation area of ​​dry lowland plants with various collections of plant habitus, both from trees, shrubs, herbs, lianas, and others. other. The existence of butterflies in a habitat has a role as pollinating insects which have a very important position in maintaining the balance of nature. Butterflies aside from being natural pollinating agents, can be used as an indicator in testing environmental quality, by observing the state of their habitat. This study aims to find out what types of butterflies are found in the Baning Nature Park and their ecological roles. This research is a type of exploratory research. Data collection was carried out using a belt transect, by circling the Baning Nature Park. Catching butterflies is done using sweeping technique. Observations made at the Baning Nature Park found 15 species in 4 different families. These species namely; Arhopala centaurus, Leptosia nina, Appias olferna, Eurema blanda, Catopsilia pomona, Eurema hecabe, Junonia hedonia, Junonia atlites, Junonia iphita, Hypolimnas bolina, Phaedyma columella, Elymnias hypermnestra, Tanaecia trigerta, Papilio memnon, and Papilio polytes. The ecological role of the butterfly is as a pollinating organism. Nectar-producing plants in Baning Nature Park which are frequently visited by butterflies, namely, the species Psydrax dicoccos and Ixora sp.